The measurement of psychological constructs in people with osteoarthritis of the knee: a psychometric evaluation - Lincoln, Nadina; Moreton, Bryan; Turner, K.; Walsh, David A. (Taylor & Francis, 2017)
Purpose: To examine the measurement properties of measures of psychological constructs in people with knee osteoarthritis. Method: Participants with osteoarthritis of the knee completed the beck depression inventory (BDI-II), state-trait anxiety inventory (STAI), arthritis helplessness index (AHI), fatigue severity scale (FSS), coping strategies questionnaire (CSQ), beliefs about pain control questionnaire (BPCQ), illness perceptions questionnaire-revised (IPQ-R), pain self-efficacy questionnaire (PSEQ) at home as part of a set of measures covering different aspects of osteoarthritis pain. The questionnaires were returned by pre-paid envelope. Rasch analysis was used to check the psychometric properties of the scales in people with osteoarthritis. Results: The STAI-SF was an acceptable measure of anxiety and the revised FSS an acceptable measure of fatigue, with removal of items 1 and 2. The BDI subscales were acceptable for measuring negative thoughts and behaviours related to depressive symptomatology with some modifications to the scale. The helplessness scale of the AHI was acceptable as a measure of helplessness. The PSEQ was an acceptable measure of self-efficacy and the CSQ as a measure of cognitive coping strategies. The BPCQ and IPQ-R did not fit the Rasch model. Conclusions: These findings indicate that questionnaires need to be checked for their ability to measure psychological constructs in the clinical groups to which they will be applied.